Seroprevalence of Antibodies against SARS-CoV-2 among the Personnel and Students of the National and Kapodistrian University of Athens, Greece: A Preliminary Report - Tsitsilonis, Ourania E. (Life (Basel), 2020)
Due to early implementation of public health measures, Greece had low number of SARS-CoV-2 infections and COVID-19 severe incidents in hospitalized patients. The National and Kapodistrian University of Athens (ΝΚUA), especially its health-care/medical personnel, has been actively involved in the first line of state responses to COVID-19. To estimate the prevalence of antibodies (Igs) against SARS-CoV-2 among NKUA members, we designed a five consecutive monthly serosurvey among randomly selected NKUA consenting volunteers. Here, we present the results from the first 2500 plasma samples collected during June–July 2020. Twenty-five donors were tested positive for anti-SARS-CoV-2 Igs; thus, the overall seroprevalence was 1.00%. The weighted overall seroprevalence was 0.93% (95% CI: 0.27, 2.09) and varied between males [1.05% (95% CI: 0.18, 2.92)] and females [0.84% (95% CI: 0.13, 2.49)], age-groups and different categories (higher in participants from the School of Health Sciences and in scientific affiliates/faculty members/laboratory assistants), but no statistical differences were detected. Although focused on the specific population of NKUA members, our study shows that the prevalence of anti-SARS-CoV-2 Igs for the period June–July 2020 remained low and provides knowledge of public health importance for the NKUA members. Given that approximately one in three infections was asymptomatic, continuous monitoring of the progression of the pandemic by assessing Ig seroprevalence is needed.